O empresariamento da Educação: breve análise sobre a atuação do Instituto Votorantim na educação pública - Paes, Denise Araujo (Universidade Federal de São Carlos, 2021)
The present work aims to make a brief introductory analysis about the work of Votorantim Institute in Education in the context of educational reforms developed in Brazil since 1990s. There is an increasingly frequent presence of foundations and business institutes offering education projects aimed at public education. The main goal was to analyze the performance of Votorantim Institute in public schools by analyzing the documents published on institute’s website and also by analyzing theses, dissertations and articles. The analyzes were mainly based on the following authors: Melo (2003), Neves (2005), Luz (2009), Peroni (2013) e Freitas (2014). It was observed the impact that business can make at public educations through alliances made between public and private. In the general survey on the role of education in Brazil, the public and private sectors and the growing business performance in the public school, it can understand about the importance of Brazilian public school, to go against or in favor of this current dominant hegemony.
Entrepreneurship in education: a brief analysis of the role of the Votorantim Institute in public education
Keywords: Empresariamento da educação; Público e privado; Instituto Votorantim; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO